“Are they just for venting out?” : Exploring discourses on women-only Facebook Groups on television talk show programs in Egypt - Kamel, Shaden (University of Bayreuth African Studies Working Papers, 2024)
In Egypt, many women have created various private Facebook groups for women only to support women. As exclusive spaces for women, these Facebook groups enabled women in Egypt to share their experiences and quickly became a source of awareness. Concurrently, their proliferation and popularity as spaces exclusively encompassing thousands of women have attracted extensive mass media coverage in Egypt, particularly from talk show programs. Accordingly, this article uses critical discourse analysis to explore the discourses on popular women-only Facebook groups in mainstream talk show programs in Egypt. Ten talk show program videos were analyzed to identify the discourses on these Facebook groups. The article displays conversations from four talk show program segments to showcase two prevalent and simultaneous discourses. The first discourse conveys a moral panic over these Facebook groups for enabling women to discuss problems on matters of the private sphere. Conversely, the second discourse conveys an embracement of Facebook group creators’ entrepreneurial practices manifested from their Facebook group. Subsequently, these two discourses are critically analyzed by drawing on literature on gendered dynamics of the private and public spheres in Egypt and postfeminism in connection with commercial media logic.
Keywords: Talk shows; media discourses; Facebook groups; women-only spaces; television; Egypt